The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1002/(sici)1096-9861(19960610)369:4<591::aid-cne8>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

TRK and p75 neurotrophin receptor systems in the developing human brain

Abstract: The prenatal development of the neurons immunoreactive for high-affinity tropomycin-related kinase (trk) receptor (pan trk which recognizes trkA, trkB, and trkC) and low-affinity p75 neurotrophin receptor (p75NTR) was examined in the human brain from embryonic weeks 10 to 34 of gestation. In the embryonic week 10 specimen in which only brainstem regions were available for evaluation, trk immunoreactivity (trk-ir) was observed in the ventral cochlear, solitary, raphe, spinal trigeminal, and hypoglossal nuclei, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 95 publications
3
13
0
Order By: Relevance
“…In layer 1, trkB TK+ mRNA-positive cells were observed throughout the postnatal life of humans. While the identity of the trkB TK+ mRNA-positive cells found in the human subcortical white matter or in layer I was not determined in our study, other groups have demonstrated that subplate neurons and layer I Cajal-Retzius (CR) cells express trkB in rodent brain, and that subplate neurons express pan-trk in the developing human brain (Cabelli et al, 1996;Chen et al, 1996;Fukumitsu et al, 1998;Ringstedt et al, 1998). Recent evidence suggests that CR cells continue to exist in the adult human prefrontal cortex (Martin et al, 1999).…”
Section: Expression Of Trkb Tk T In Dlpfc: Anatomymentioning
confidence: 59%
“…In layer 1, trkB TK+ mRNA-positive cells were observed throughout the postnatal life of humans. While the identity of the trkB TK+ mRNA-positive cells found in the human subcortical white matter or in layer I was not determined in our study, other groups have demonstrated that subplate neurons and layer I Cajal-Retzius (CR) cells express trkB in rodent brain, and that subplate neurons express pan-trk in the developing human brain (Cabelli et al, 1996;Chen et al, 1996;Fukumitsu et al, 1998;Ringstedt et al, 1998). Recent evidence suggests that CR cells continue to exist in the adult human prefrontal cortex (Martin et al, 1999).…”
Section: Expression Of Trkb Tk T In Dlpfc: Anatomymentioning
confidence: 59%
“…In particular, ChAT-positive, p75-negative neurons have been reported in the nucleus basalis-substantia innominata complex, whose fibers have been surmised to project to the amygdala and parts of the rhinal paralimbic areas (Heckers et al 1994). An absence or decrease in the p75 receptor has been demonstrated in the amygdala of rodents (Yan and Johnson 1988) as well as in the entorhinal cortex of humans (Kordower and Mufson 1992;Chen et al 1996). This may explain the relative sparing of ChAT observed in immunotoxintreated animals in the entorhinal-piriform cortex and the amygdala (Heckers et al 1994;Schliebs et al 1996).…”
Section: Discussionmentioning
confidence: 97%
“…It is known that CGRP-expressing primary afferent neurons, serotonergic neurons in the Raphe nuclei, noradrenergic neurons of the locus ceruleus and dopaminergic neurons of the hypothalamus all express p75 in several species, including humans (Sobreviela et al, 1994;Berg-von der Emde et al, 1995;Wright & Snider, 1995;Chen et al, 1996;Yamuy et al, 2000), implicating a possible direct role for p75 NTR in suppressing spinal plasticity. TH-expressing axons in the substantia nigra pars compacta, some of which also project spinally, do not express p75 NTR (Chaisuksunt et al, 2003) so, if these axons sprout after rhizotomy and ⁄ or neurotrophic factor treatment, the underlying mechanism is likely to be p75 NTR independent.…”
Section: Discussionmentioning
confidence: 99%
“…The present results represent the first report of decreased spinal innervation by descending monoaminergic axons in p75-⁄ -mice. While these axonal phenotypes are known to express p75 NTR (Sobreviela et al, 1994;Berg-von der Emde et al, 1995;Chen et al, 1996;Yamuy et al, 2000), it remains unknown whether the decrease in spinal axon density is due to a developmental decrease in neuronal number and ⁄ or to a decrease in spinal branching.…”
Section: Discussionmentioning
confidence: 99%